Podridão abacaxi da cana-de-açúcar: reação de variedades, controle químico e diversidade patogênica - Uzan, Juliana (2019)
Brazil is the world's largest producer of sugarcane, and its main products are sugar, ethanol and biomass. With the high demand for its products, there was a need to plant it all year round. Thus sugarcane pineapple disease, became a problem in winter plantings. The soil pathogen Thielaviopsis paradoxa infects newly planted grinding seedpieces, causing major failures in the field. The genetic resistance of cultivars presents as the ideal method of control, however, there are no reports of the resistance of the four cultivars studied in this work. Chemical control is an alternative to susceptible cultivars. Aiming to analyze the reaction to T. paradoxa of four sugarcane cultivars, its control with fungicide, and the pathogenic diversity of fungus isolates, four trials were installed: 1st experiment (analyzed at 28 days) and the trays containing substrate inoculated with T. paradoxa (105, 104, 10³, 10² spores.mL-1 and Control) and individualized buds of the cultivars RB867515, RB966928, RB855156 and RB92579 were used in the 2nd experiment (analyzed at 40 days) ; less (RB867515) and more (RB92579) susceptible to the pathogen, new buds were planted in trays, using substrate inoculated with 104 and 107 spores.mL-1 and Control, with the application of Strobilurin + Triazole. For the fourth experiment, five buds of the four cultivars were used, and suspensions of 105 spores.mL-1 of five T. paradoxa isolates were inoculated at both ends of the grinding seedpieces. The substrate of experiments 1, 2 and 3 was maintained at 25% humidity and all experiments were maintained in a controlled environment with a temperature of 20°C and photoperiod of 12h. In experiments 1, 2 and 3 the sprouting rate and final sprouting were analyzed at 28 days (experiments 1 and 3) and at 40 days (experiment 2), in experiment 4 the necrotic area inside the grinding seedpieces was measured. The data were transformed into percent and submitted to analysis of variance by the Tukey test at 5% probability. The results showed that the cultivar RB867515 was the least susceptible and the most susceptible RB92579; the intermediate cultivars RB966928 and RB855156; the fungicide with the combination of the active principles Strobilurin + Triazol presented potential for the control of T. paradoxa; there is pathogenic diversity among isolates of T. paradoxa obtained from different lesions and even field in sugarcane producing areas of Brazil.